2003
DOI: 10.4141/a03-029
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting embryo survival and strategies to reduce embryonic mortality in cattle

Abstract: Bilodeau-Goeseels, S. and Kastelic, J. P. 2003. Factors affecting embryo survival and strategies to reduce embryonic mortality in cattle. Can. J. Anim. Sci. 83: 659-671. Embryonic mortality in cattle is the death of the conceptus before Day 42 of pregnancy. Estimates of embryonic mortality varied greatly, ranging from 10 to 40% in first-service cattle to 65% in repeat-breeder cows. This paper reviews endogenous causes of embryonic mortality, including chromosomal abnormalities, inadequate corpus luteum functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 146 publications
(126 reference statements)
0
17
0
1
Order By: Relevance
“…Previous studies reported that the embryo transfer to the cranial third of the embryo during the embryo transfer increased the pregnancy rate (Beal, Hinshaw, & Whitman, ; Bó et al, ; Roper et al, ; Scenna et al, ). Normally the embryo reaches from the oviduct into the uterus approximately 6–8 days after fertilization (Bilodeau‐Goeseels & Kastelic, ). Therefore, in uterine flushings on day 7, embryos are mostly collected from the cranial part of the uterine horn (Gordon, ; Niemann & Wrenzycki, ; Sponchiado et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the embryo transfer to the cranial third of the embryo during the embryo transfer increased the pregnancy rate (Beal, Hinshaw, & Whitman, ; Bó et al, ; Roper et al, ; Scenna et al, ). Normally the embryo reaches from the oviduct into the uterus approximately 6–8 days after fertilization (Bilodeau‐Goeseels & Kastelic, ). Therefore, in uterine flushings on day 7, embryos are mostly collected from the cranial part of the uterine horn (Gordon, ; Niemann & Wrenzycki, ; Sponchiado et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Acute negative energy balance in intensively managed North American cattle herds has been reported as a cause of embryo mortality (Vanroose et al, 2000;Bilodeau-Goeseels and Kastelic, 2003). Periods of acute negative energy balance occur on an annual basis in tropical regions of Australia and as a consequence could be associated with embryo mortalities in beef cattle herds in these regions.…”
Section: Extended Periods Of Low-rainfallmentioning
confidence: 99%
“…However, attention has recently shifted towards the widely reported fall in conception rates (Bousquet et al. ; Roche ) and a remarkably high incidence of early embryonic mortality (Mann and Lamming ; Bilodeau‐Goeseels and Kastelic ). How suboptimal maternal metabolism or nutrition in the dairy cow can affect oocyte and embryo quality has been reviewed extensively (Leroy et al.…”
Section: Introductionmentioning
confidence: 99%